A systematic review indicates an association between birth weight and body fat in childhood. (15th March 2021) - Rallis, Dimitrios; Balomenou, Foteini; Tzoufi, Meropi; Giapros, Vasileios
Abstract: Aim: To summarise the existing evidence regarding the body fat of small or large for gestation subjects, evaluated from birth up to 18 years of age. Methods: The PRISMA guidelines were adopted for the current systematic review, including studies having evaluated body fat with bioelectrical impedance analysis, air displacement plethysmography, dual‐energy X‐ray absorptiometry or magnetic resonance imaging. Results: A total of 31 studies was included. The balance of evidence suggests that small for gestation infants have decreased fat mass at birth; postnatally they experience increased adiposity. In the long term, however, the evidence is inconclusive, since some studies suggest that foetal‐restricted children with increased catch‐up growth are at increased risk of fat accumulation, whereas other studies suggest a neutral or even negative association. Large for gestation infants have increased fat mass at birth, but in the long term, they have a lower body fat ratio, especially when they develop a catch‐down growth. Conclusion: Some studies suggested that foetal‐restricted children with increased catch‐up growth are at increased risk of later adiposity, while other studies suggested a neutral or negative association. Given that the evidence is inconclusive, further studies are warranted. Large for gestation subjects have lower body fat when they develop catch‐down growth.